2014
DOI: 10.1039/c3ce41773e
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing crystal growth by oriented aggregation

Abstract: Oriented aggregation (OA) is a non-classical crystal growth mechanism by which uniquely shaped nanocrystals with tight size control can be produced. Primary crystallites attach with crystallographic order, leading to the formation of secondary, single crystals. Comprehensive characterization is critical for elucidating the fundamental processes of oriented aggregation. Transmission electron microscopy (TEM), cryogenic TEM, and in situ fluid cell TEM enable direct imaging of materials throughout the growth proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 90 publications
4
74
0
Order By: Relevance
“…Finally, ultraviolet-visible (UV-Vis) spectroscopy can be used to determine size from size-dependent optical properties of some nanoparticles [89], though this technique has less applicability to nanoparticles (including some iron oxides) that do not change color or optical properties with size. An in-depth review of methods for characterizing growth via OA can be found in Penn and Soltis [28].…”
Section: Correlative Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, ultraviolet-visible (UV-Vis) spectroscopy can be used to determine size from size-dependent optical properties of some nanoparticles [89], though this technique has less applicability to nanoparticles (including some iron oxides) that do not change color or optical properties with size. An in-depth review of methods for characterizing growth via OA can be found in Penn and Soltis [28].…”
Section: Correlative Methodsmentioning
confidence: 99%
“…The detection of features such as crystal twinning, dislocations, and dimpled boundaries in TEM images can indicate relics of growth by OA [28]. Figure 11.4 shows a pair of TEM images of goethite synthesized from a ferrihydrite precursor [51].…”
Section: Imagingmentioning
confidence: 99%
See 3 more Smart Citations